Modifikasi Lapisan Tungku Bakar Dan Kecepatan Aliran Udara untuk Meningkatkan Kinerja Kompor Oli Bekas - Aditya Syah; Muhamad Hidayat; Mietra Anggara; Aldrin Aldrin (Jurnal GEAR (Energi, Perancangan, Manufaktur & Material), 2026)
This research is motivated by the increasing price and scarcity of 3 kg LPG in Indonesia, particularly in Dompu Regency, West Nusa Tenggara, which burdens the low-income community. In addition, the abundant waste lubricating oil from motor vehicles poses an environmental hazard if not utilized properly. The objective of this study is to modify a prototype of a used oil stove to enhance its thermal performance evaluated through the Water Boiling Test (WBT) method. The methodology involves computer-aided mechanical design followed by adding a 6 mm fiberglass insulation layer around the combustion chamber and integrating an internal air flow control valve in the inlet pipe. The experiments were conducted using four operational variables combining air pressure levels and insulation states for boiling 3 liters of water. The results demonstrated that the maximum flame temperature reached 270°C under high air pressure combined with fiberglass insulation. The highest thermal efficiency achieved was 37% with a fuel consumption rate of 19.63 g/min, yielding an input power of 196.25 W and an output power of 71.74 W. The modification successfully elevated the stove's thermal performance, providing a cost-effective and eco-friendly energy alternative.